Building bridges for empowerment and informed decision-making: A qualitative study of midwives’ reflections on how to optimise contraceptive counselling for immigrant women in Sweden - Mia Kolak; Anette Agardh; Stefan R. Hansson; Christine Rubertsson; Maria Ekstrand Ragnar (PLoS ONE, 2026)
Background Sweden’s National Strategy for Sexual and Reproductive Health and Rights (SRHR) emphasises equitable access to contraception and abortion services. Despite this, immigrant women in Sweden experience lower contraceptive use and higher rates of unintended pregnancies and abortions compared with native-born women. Midwives, as primary providers of contraceptive counselling and prescribing, play a central role in promoting reproductive autonomy and informed choice. Aim To explore midwives’ reflections on how to optimise contraceptive counselling for immigrant women in Sweden. Methods Eleven focus group discussions were conducted with 50 midwives from public and private midwifery clinics in Malmö, where one-third of residents are foreign-born. Data were analysed using qualitative content analysis. Findings The overarching theme, “Building bridges for empowerment and informed decision-making,” captured midwives’ commitment to promoting women’s autonomy while navigating systemic and cultural challenges. Five sub-themes emerged: overcoming the discrepancy between mission and reality; addressing organisational weaknesses in the care chain; enhancing knowledge and capabilities; reinforcing competence and trust in communication; and involving men without undermining women’s autonomy. Midwives highlighted structural barriers, limited resources, and time constraints that hindered person-centred and culturally sensitive care. Conclusion Optimising counselling for immigrant women requires systemic changes, including revised funding structures, expanded multilingual resources and strengthened professional development. Addressing these barriers will enhance women's capabilities and support their reproductive autonomy, aligning with Nussbaum’s Capabilities Approach and promoting gender equality.